Strategi Komunikasi Persuasif BPBD (Badan Penanggulangan Bencana Daerah) Provinsi Sumatera Selatan Dalam Mengatasi Kebakaran Lahan Gambut Di Kota Terpadu Mandiri (KTM) Sungai Rambutan Ogan Ilir - Adriansyah , Hafis; Syarifudin , Achmad; Isnaini , Mohd Aji (CV. ITTC INDONESIA, 2023)
This research is about persuasive communication with the title Persuasive Communication Strategy BPBD (Regional Disaster Management Agency) of South Sumatra Province in Overcoming Peatland Fires in the Independent Integrated City (KTM) Sungai Rambutan Ogan Ilir. This research uses a qualitative method that is naturalistic because the research is carried out in natural conditions (natural setting) with theory. The data source in this study is qualitative data expressed in the form of words that have meaning. In this study, the data was sourced from interviews with informers from the BPBD (Regional Disaster Management Agency) of South Sumatra Province. The results of the study show that the BPBD of South Sumatra Province uses persuasive communication as an appropriate and effective step, to invite or influence, to change the attitude/behavior of farmers/citizens. Persuasive communication can change the behavior of farmers/citizens by focusing on the issues presented, providing explanations of aims and objectives, providing examples of problems, and conveying messages using persuasive or inviting words as well as strong evidence or facts, and conveyed with care so that there is no conflict. The steps of the South Sumatra Province BPBD in the persuasive communication process are that it must be carried out in accordance with the work plan, delivered according to the objectives, the delivery is made on time, the delivery is also right on target and the persuasion is conveyed properly and correctly. Meanwhile, the obstacles experienced were that the residents/farmers were not aware of the consequences of the behavior of burning the land, did not know the consequences of burning and there were some residents/farmers who felt that the message conveyed would hinder their activities.